Thomas Jefferson : In His Own Words. - Baron, Robert C. (Speaker's Corner., 2009)
"We are not to expect to be translated from despotism to liberty in a featherbed."Thomas Jefferson, letter to Marquis de Lafayette, 1790 Thomas Jeffersonauthor of the Declaration of Independence and third president of the United Statesvoiced the hopes of a new America with eloquence and passion. Focusing on the personal side of Jefferson, this wonderful collection explores his ideas and legacy through his letters and writings. With subjects ranging from his views on exploration, freedom, and democracy to ruminations on friends, family, books, and gardening, Thomas Jefferson: In His Own Word.